ANALISIS UNJUK KERJA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) ATAP 30 kWp KANTOR DINAS PERHUBUNGAN PROVINSI BALI - Rahmawati, Susi; Kumara, I.N.S; Suyadnya, I.M.A (Jurnal SPEKTRUM; Vol 12 No 1 (2025): Jurnal SPEKTRUM, 2025)
Rooftop PLTS is one that is quite promising, but its number in Indonesia is not much. The Central Government provides a Rooftop PLTS grant to the Bali Provincial Transportation Agency with an installed capacity of 30 kWp with an On Grid system in order to expand the system capacity. This study was conducted to determine the potential and savings of the installed PLTS using the PVsyst program simulation. Based on the results of the study, the results of the simulated PLTS production were 32,116 kWh, a performance ratio of 78.1%, real PLTS production of 27,133 kWh and electricity consumption of 39,271 kWh before the installation of the PLTS in 2020 and 33,057 kWh after installation in 2021. The potential savings for 6 months from July to December 2021 amounted to IDR 10,786,359 or 21.50% of the total.